Staging the family unfamiliar: the queer intimacies in Ramble-Ations: A One D'Lo Show. Issue 4 (2nd October 2019) - Pérez, Kimberlee
ABSTRACT: Queer personal narratives that include family storytelling draw attention to normative conventions that produce queer family members' sexuality as a "stage" through which they pass. Simultaneously, queer personal narratives call on nonnormative discourses to generate queer worldmaking sites of kinship and belonging. In this essay, I look to the ways D'Lo's Ramble-Ations: A One D'Lo Show uses personal narrative and family storytelling to stage refusals and reconfigurations of familiar splits among race, sexuality, and gender. Using performative writing and critical analysis, I use stages and stagings to argue the family unfamiliar opens queer intimate relations with and through an audience.